The influence of housing price developments on household consumption: Empirical analysis for the Czech Republic - Sylvie Dvořáková; Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This paper studies how the change of wealth of households represented by housing prices and stock market prices influences households' consumption. We provide empirical analysis based on the Czech aggregate data from 1998-2009. We analyse the effect of change in households' wealth on the consumption of both durable and non-durable goods employing the VAR and VEC models on quarterly data. The robustness of results is verified by Dynamic OLS and Fully Modified OLS framework. We find a positive effect of both housing wealth and stock market wealth on both types of consumption. In case of non-durable goods consumption, we estimate the cointegrating vector and conclude that the elasticity of non-durable goods consumption with respect to housing wealth is over three times greater than with respect to stock market wealth.
Keywords: C22; E39; G12; 330; households; housing prices; consumption; housing wealth; stock market wealth; VAR model; VECM